IMMUNOMODULATORY ACTIVITY OF THE CHENOPODIUM OPULIFOLIUM TOTAL CRUDE EXTRACT IN WISTER ALBINO RATS - Tibitondwa, Josephine; Ikwap, Kokas; Tamale, Andrew; Tamale, Andrew; Tumwine, Gabriel; Kateregga, John; Wamala, Samuel P.; Kato, Charles D. (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Chronic disease conditions like cancer, diabetes, malnutrition and HIV/AIDS compromise the immune system thus necessitating immune boasting. The use of medicinal herbs in immunomodulation is now common, albeit with limited evidence regarding efficacy. We therefore investigated the immunomodulatory activity of the total crude leaf and stem extract of Chenopodium opulifolium in mice. Materials and methods: An experimental study was conducted using four groups of rats each with 6 animals with treatments administered daily for 29 days. Group one served as the positive control and received 20mg/kg of levamisole. Group 2, the negative control received 2 ml of an olive oil and normal saline mixture. Groups 3 and 4 received 100mg/kg and 200mg/kg bwt of the total crude leaf and stem extract respectively. On the 15th day, whole blood was collected for complete blood count and delayed type hypersensitivity response determination, haemagglutination antibody titer assay was done on blood collected on the 29th day. Results: Results revealed that the extract had a significant (P< 0.05) effect on haemagglutination antibody titers with the highest response observed in the extract group at 200mg/kg (30.67±1.33). The mean WBC (3.13±0.71×103/μl), neutrophil (0.93±0.48 cells/ μl) and lymphocyte (2.20±0.00 cells/ μl) counts in the 200mg/kg bwt extract group were elevated to levels comparable to the positive control. Conclusion: The total crude extract of Chenopodium opulifolium exhibits immunomodulatory activity in a dose dependent manner. Future studies utilizing pure extracts in order to pin point to the extract mechanism responsible for Immunomodulation are required for more conclusive results.